(untitled) (Journal of Global Accounting, 2025)
This study ascertained the effect of social responsibility disclosure on sustainable development of listed industrial goods firms in Nigeria. Thirteen (13) listed industrial goods firms constituted the sample size of this study between 2011 and 2023. Ex-Post facto research design and content analysis were adopted while secondary data were extracted from the annual reports and accounts of the sampled firms and were analysed using E-Views 10.0 statistical software. The study employed inferential statistics using Pearson correlation and Binary Probit regression analysis. Three hypotheses were formulated and statistically tested at 5 per cent level of significance using regression analysis. Findings from the empirical analysis showed that that environmental social responsibility disclosure has a significant and positive effect on waste recycling (β1 = 1.787941; p-value = 0.0250<0.05); ethical social responsibility disclosure has a significant and positive effect on waste recycling (β2 = 0.458946; p-value = 0.0087<0.05); philanthropic social responsibility disclosure has a significant and positive effect on waste recycling (β3 = 6.902677; p-value = 0.0000<0.05). The study further concludes that the components of social responsibility disclosure considered in this study are important variables in influencing sustainable development of listed industrial goods firms in Nigeria. It was recommended inter alia that firms should be environmentally friendly to enable them gain competitive advantage, high liquidity and reduced environmental cost in the long run, thereby leading to a sustainable development.